Using Meta-Models for Tsunami Hazard Analysis: An Example of Application for the French Atlantic Coast - Bacchi, Vito; Jomard, Hervé; Scotti, Oona; Antoshchenkova, Ekaterina; Bardet, Lise; Duluc, Claire-Marie; Hebert, Hélène (Frontiers in Earth Science, 2020)
This paper illustrates how an emulator (or meta-model) of a tsunami code can be a useful tool to evaluate or qualify tsunami hazard levels associated with both specific and unknown tsunamigenic seismic sources. The meta-models are statistical tools permitting to drastically reduce the computational time necessary for tsunami simulations. As a consequence they can be used to explore the tsunamigenic potential of a seismic zone, by taking into account an extended set of tsunami scenarios. We illustrate these concepts by studying the tsunamis generated by the Azores-Gibraltar Plate Boundary (AGPB) and potentially impacting the French Atlantic Coast. We first analyze the impact of two realistic scenarios corresponding to potential sources of the 1755-Lisbon tsunami (when uncertainty on seismic parameters is considered). We then show how meta-models could permit to qualify the tsunamis generated by this seismic area. All the results are finally discussed in light of tsunami hazard issued by the TSUMAPS-NEAM research project available online (http://ai2lab.org/tsumapsneam/interactive-hazard-curve-tool/). From this methodological study, it appears that tsunami hazard issued by TSUMAPS-NEAM research project is envelop, even when compared to all the likely and unlikely tsunami scenarios generated in the AGPB area.